Persepsi Orang Tua terhadap Penggunaan Gadget pada Anak Usia 5-6 Tahun - Faridah Faridah; Iin Indrawati (Prosiding Seminar Kesehatan Nasional, 2022)
Gadget are a technology that cannot be released nowadays, including children who use gadget to watch videos, play educational or adventure games. The introduction of gadgets from an early age is very good, because gadget have many benefits that can help humans carry out their activities. However, too early recognition is feared to have an impact on children. This impact can be either a negative impact or a positive impact. The purpose of this study was to describe parents' perceptions of gadget use in children aged 5-6 years. This study uses a qualitative descriptive approach. The results of this study were 32 respondents with an average senior high school 66% (21 people), parents' understanding of gadget was categorized as good 72% (23%), parents' attitudes towards children in using gadget were categorized as good 78% (25 people), so it can be concluded that parents' perceptions of using gadget are good, meaning that parents understand the positive and negative impacts of using gadget. This research is expected to help parents understand the use of gadgets so that children's growth and development can be monitored optimallyÂ